Effects of psychological interventions for patients with osteoarthritis: a systematic review and meta-analysis. Issue 1 (2nd January 2018) - Zhang, Lijuan; Fu, Ting; Zhang, Qiuxiang; Yin, Rulan; Zhu, Li; He, Yan; Fu, Wenting; Shen, Biyu
Abstract: The aim of this study was to determine the effects of psychological interventions (e.g. cognitive restructuring, relaxation) on physiological and psychological health in osteoarthritis patients. A systematic literature search was done using PubMed, Embase, PsycINFO, Web of Science, China National Knowledge Infrastructure, and Wanfang Database through November 2016. Studies were included if they used a randomized controlled trial designed to explore the effects of psychological interventions in osteoarthritis patients. Two independent authors assessed the methodological quality of the trials using criteria outlined by Jadad et al. Meta-analysis was done with the Revman5.0. Twelve randomized controlled trials, including 1307 osteoarthritis patients, met the study inclusion criteria. Meta-analysis showed that psychological interventions could reduce the levels of pain [standard mean difference (SMD) −0.28, 95% CI −0.48, −0.08, P -value 0.005)] and fatigue (SMD −0.18, 95% CI −0.34, −0.01, P -value 0.04). In addition, psychological interventions significantly improved osteoarthritis patients' self-efficacy (SMD 0.58, 95% CI 0.40, 0.75, P -value 0.00) and pain coping (MD 1.64, 95% CI 0.03, 3.25, P -value 0.05). Although the effects on physical function, anxiety, depression, psychological disability were in the expected direction, they were not statistically significant. In conclusion, the role of psychological interventions in the management of osteoarthritis remains equivocal. Some encouraging results were seen with regard to pain, pain coping, self-efficacy, and fatigue. We believe that more methodologically rigorous large-scale randomized controlled trials are necessary to answer this study question.